2014
DOI: 10.1002/cncr.28819
|View full text |Cite
|
Sign up to set email alerts
|

Public education and targeted outreach to underserved women through the National Breast and Cervical Cancer Early Detection Program

Abstract: The National Breast and Cervical Cancer Early Detection Program (NBCCEDP) was established to provide low-income, uninsured, and underinsured women access to cancer screening and diagnostic services with the goal of increasing the early detection and prevention of breast and cervical cancer. Although this is a valuable resource for women who might not have the means to get screened otherwise, providing services at no cost, by itself, does not guarantee uptake of screening services. Public education and targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 12 publications
0
35
0
1
Order By: Relevance
“…In this study, the use of the SEM encouraged us to develop a multi-layered intervention that could draw on interpersonal, community, cultural, and structural aspects of health 17 . The findings indicate that the women participating experienced direct personal benefit with regard to their interactions, particularly with family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the use of the SEM encouraged us to develop a multi-layered intervention that could draw on interpersonal, community, cultural, and structural aspects of health 17 . The findings indicate that the women participating experienced direct personal benefit with regard to their interactions, particularly with family members.…”
Section: Discussionmentioning
confidence: 99%
“…The SEM offers a framework to advance thinking beyond increasing access to existing services to also considering the need for a multi-level understanding of health that draws on interpersonal, community, cultural, and structural aspects 17 . The SEM encourages the consideration of multiple factors that may influence mental health, including the adaptation to a new country, the influence of faith 18 , and specific cultural practices that influence perspectives on health 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Steadily growing new cases, high mortality rate combined with lack of radical cures have made prevention and early diagnosis priority strategies stemming the epidemic (Jemal, 2012;Caplan, 2014;Tarraga-Lopez et al, 2014). Tremendous efforts have been invested on public education (e.g., disseminating prevention information via various mass media) (Levano et al, 2014;Seven et al, 2014), screening service, and drug prevention (e.g., use of tamoxifen) and treatment of precancerous conditions (e.g., polyps, Helicobacter pylori infection) (Gao et al, 2013;Hady et al, 2013;Lansdorp-Vogelaar et al, 2013). However, there exists a big gap between actual implementation of preventions and expectations (Gupta et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Acculturation has not been associated with perceived worry for breast cancer among immigrant women who are Latina and of other ethnicities (April-Sanders, Oskar & Shelton, 2016). However, evaluation findings of the national BCCEDP program have shown that targeted educational programs and collaborating with community-based organizations to implement these programs were effective strategies to reach poor and less acculturated women (Levano, Miller, Leonard, et al, 2014). Research on the relationships between health perceptions, health behaviors, and acculturation for ethnically diverse Black women is an emerging area of research and thus is not well understood.…”
Section: Ethnic Variations In Health Perceptionsmentioning
confidence: 99%
“…. The Center for Disease Control and Prevention has developed a Guide to Community Preventive Services that contains recommendations for evidence-based interventions that are effective strategies to increase breast and cervical cancer screening (Levano et al, 2014). Staff would benefit from accessing this resource and reviewing the various strategies implemented nationally by grantees to deliver educational activities and to foster collaborations in communities for the purposes of sustainability and saturation within targeted locations.…”
Section: Recommendations For Practicementioning
confidence: 99%